The Iceberg Model of Change: A taxonomy differentiating approaches to change - Christian A. Mahringer; Laura Schmiedle; Lisa Albicker; Simone Mayer (Heliyon)
Change is a ubiquitous phenomenon, but different scientific communities conceptualize change differently, which hampers conceptual clarity. This conceptual paper, which is based on a review of the literature on change, addresses this problem by developing the ‘Iceberg Model of Change’. This framework distinguishes three approaches to change: objectification, distinction, and unfolding. The objectification approach treats processes of change as things with symbolic properties, which can be used to steer societal and political discourse, reveal thematic relationships across studies, and emphasize the significance of work. This approach also tends to consider change as a variable (dependent or independent) that can be used to understand antecedents and consequences. The distinction approach conceptualizes change as a series of discrete states of an entity or system at multiple points in time or as phases, enabling comparison of those states. The unfolding approach considers how change processes develop, including the complex, interrelated mechanisms underpinning change. Here, line graphs, visualizations of interaction mechanisms, and trajectories are used to capture change. This framework contributes to research, a) by enabling a comprehensive consideration of change phenomena, b) by promoting interdisciplinary collaboration when project partners differ in their assumptions about change, and c) by emphasizing the need for methodological reflexivity.